Investing in PV Systems utilizing Savings from Building Envelop Replacement by Sustainable Local Material: A Case Study in Lebanese Inland Region - Farhat, Raghid; Ghaddar, Nesreen K.; Ghali, Kamel (International Journal of Energy Economics and Policy, 2014)
In this work, we propose to reduce the initial building construction cost by using local low-embodied energy materials and use savings to offset the cost of renewable energy installations. A typical house in the desert climate of inland Lebanon is modeled using commercial software for a conventional construction case and when using local construction materials. The savings from envelop replacement were used to invest in installing a solar water heater (SWH), and a photovoltaic (PV) system as well as double glazed windows. This resulted in net energy savings up to 97% and 59% for single and double glazed windows, respectively. When further investment in the PV system is evaluated and optimized based on life cycle cost, the savings from covering the electrical load and selling to the grid decreased respectively to 27% and 75% in the case of single glazing and to 28% and 76% in the case of double glazing. Keywords: Local construction material; Initial construction cost; PV system design and optimization; Renewable Energy JEL Classifications: C61; C63; L94; Q20; Q28